Preoperative neutrophil-to-lymphocyte ratio predicts the surgical outcome of Xp11.2 translocation/TFE3 renal cell carcinoma patients - Sezim Agizamhan; Feng Qu; Ning Liu; Jing Sun; Wei Xu; Lihua Zhang; Hongqian Guo; Weidong Gan (BMC Urology, 2018)
Abstract Background The preoperative neutrophil-to-lymphocyte ratio (NLR), C-reactive protein/albumin ratio (CRP/Alb ratio) and platelet-to-lymphocyte ratio (PLR) have been demonstrated to predict the clinical outcome of various human cancer, including renal cell carcinoma(RCC). The aim of our study was to explore the prognostic values of these ratios in patients with Xp11.2 translocation/TFE3 gene fusions renal cell carcinoma (Xp11.2 tRCC). Methods A retrospective multicentre study was performed in 82 Xp11.2 tRCC patients who underwent radical or partial nephrectomy. The optimal cutoff values of the NLR, CRP/Alb ratio and PLR were determined by the receiver operating characteristic (ROC) analysis. The impact of the NLR, CRP/Alb ratio and PLR, as well as other clinicopathological characteristics, on disease-free survival (DFS) and overall survival (OS) were evaluated using the univariate and multivariate Cox regression analyses. Results The optimal cutoff values of the NLR, CRP/Alb ratio and PLR were set at 2.45, 140 and 0.08, respectively, according to the ROC analysis. Univariate analyses showed that the NLR, CRP/Alb ratio and PLR all were associated with DFS of Xp11.2 tRCC patients (P < 0.001, P = 0.005 and P = 0.001, respectively) and OS of Xp11.2 tRCC patients (P = 0.016, P = 0.003 and P = 0.014, respectively). Multivariate analysis indicated that the NLR was independently associated with DFS of Xp11.2 tRCC patients (hazard ratio [HR]: 4.25; 95% confidence interval [95% CI]: 1.19–15.18; P = 0.026) along with age (P = 0.004), the pT status (P < 0.001) and the pN status (P < 0.019), and the NLR (HR: 26.26; 95% CI: 1.44–480.3; P = 0.028) also was independently associated with OS in patients with Xp11.2 tRCC, along with age (P = 0.016) and a tumour thrombus (P = 0.007). Conclusion Overall, relatively high NLRs, CRP/Alb ratios and PLRs were associated with a poor prognosis of Xp11.2 tRCC patients; among of them, only the NLR independently predicted the progression of Xp11.2 tRCC, and the NLR may help to identify patients with high metastasis or relapse risk.